Relationship of herd average somatic cell count and spontaneous recovery from subclinical mastitis - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1985)
The rate of spontaneous recovery from subclinical mastitis was evaluated in 56 Kansas. DHI herds participating in the Somatic Cell Count (SCC) program. Herds were classified as low (>300,000) or high (>600,000) based on herd sec average. Comparisons between low and high SCC-herds were made for each cow's ability to recover from a subclinical case of mastitis (>600,000 SCC). Low-SCC herds had a rate of spontaneous recovery that was more than three times greater than that of high-SCC herds. Average SCC of cows with subclinical mastitis was similar in low and high herds J as well as the average sec of cows following spontaneous recovery. Results illustrate the importance of monitoring monthly sec reports. Proper attention to good procedures of milking management includes: attention to milking techniques, proper function of milking equipment, and attention to sanitation and housing conditions. As a result, herds with low SCC tests will have higher production and fewer subclinical cases of mastitis.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Somatic cell count; Mastitis; Production